Education, migration and family relations between China and the UK : the transnational one-child generation - Tu, Mengwei (Bingley, U.K. : Emerald Publishing Limited, 2018)
'Migration, Education and Family Relations between China and the UK: The Transnational One-Child Generation' provides a fresh perspective on the understanding of transnational families, examining the one-child generation of Chinese migrants who came to the UK to study, and their parents who remain in China, separated from their only child. As these highly-educated, capital-bearing Chinese migrants continue to pursue their careers and establish families in the West, a deeply significant dilemma emerges: as the only child in the family, how do they balance their personal aspirations with responsibilities to their parents? This study is based on interviews conducted with the one-child generation of Chinese migrants in the UK and their parents in China. It charts the life course of these migrants, from their upbringing in China, to their decision to study overseas, and establish their lives abroad. Both children and parents reveal the human complexity that lies behind these choices regarding transnational mobility and immobility, temporal and spatial changes that have challenged the basis of traditional Chinese family values, which dominated intergenerational relations in China for more than two thousand years. Ultimately, this fascinating book demonstrates that the shifting multidimensional nature of an individual's identity demands a re-examination of definitions of international students, migrants, and family.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Intergenerational relations -- China; Intergenerational relations -- Great Britain; Education, Higher -- Great Britain; Social Science, Emigration & Immigration; "Migration, immigration & emigration".